Strengthening Special Education Students Skills Through Project-Based Learning in Mathematics - Johnson, Cara (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2021)
The purpose of this manuscript is to inform and explain the effectiveness of Project-Based Learning (PBL) in mathematics. It particularly focuses on the importance of PBL for students with learning disabilities. The manuscript will explore the advantages of both cognitive and social skill building that PBL offers. Project-based learning should be utilized regularly in the classroom with special education students to help develop critical skills. This approach to mathematics is beneficial to students who may struggle to see the big picture or the relevance of mathematical concepts. Project-based learning is a way to engage the learner, drive student inquiry, and present real-world applications. Research implies that mathematical reasoning is in fact taking place through project-based learning tasks.